Testes laboratoriais para a avaliação do desempenho germinativo no campo de sementes de lotes de soja (Glycine max (L.) Merrill - Salum, Juliane Dossi [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
This research work was carried out on the campi of Jaboticabal, a unit of the Paulista State University (UNESP), Piracicaba, a unit of the University of São Paulo (USP), and Fernandópolis, a unit of the Camilo Castelo Branco University, the three of them localities of the state of São Paulo, Brazil. The objective of this work was the evaluation of some laboratory tests for the analysis of soybean seeds quality as to their efficiency in forecasting seed lots germinative performance in the field. The environmental conditions in Jaboticabal, Piracicaba, and Fernandópolis were within the limits usually found under normal agricultural practice. Nine commercial soybean seed lots were used whose vigor levels previous laboratory tests showed to be high, medium, and low. The laboratory tests were the following: standard germination, germination first count, accelerated aging, electrical conductivity, cold, seedling length according to procedures found in ISTA (1995), seedling length according to procedures found in ABRATES (1999), seedling dry matter and field emergence at the three localities. The results indicate that soybean seed companies have a reasonably high number of laboratory tests among which to choose, all of them yielding highly trustable results. The accelerated aging, the electrical conductivity, and the cold tests would be those of the highest precision. The electrical conductivity test, in addition to being of high precision, was found to be the fastest one. In addition to those, the seed company still has a high number of tests from which to choose. Among them, those in which seedling length is measured were found to be more efficient than those in which seedling dry matter is measured. The seedling length tests have a duration between 128 and 151 hours. The measuring of seedling length according to... (Complete abstract, click electronic access below)

trabalho foi desenvolvido na Faculdade de Ciências Agrárias e Veterinárias do Câmpus de Jaboticabal (UNESP), na Escola Superior de Agricultura “Luiz de Queiroz” em Piracicaba (USP) e na Universidade Camilo Castelo Branco (UNICASTELO) em Fernandópolis, e teve por objetivo verificar a eficiência de alguns testes de vigor, conduzidos em laboratório, na previsão do desempenho germinativo de sementes de lotes de soja quando semeados sob condições de campo compatíveis com a prática agrícola. Foram avaliados nove lotes de sementes por meio dos seguintes testes laboratoriais: primeira contagem, padrão de germinação, envelhecimento acelerado, condutividade elétrica, frio, comprimento de plântula de acordo com procedimentos recomendados pela ISTA (1995), comprimento de plântulas de acordo com procedimentos recomendados pela ABRATES (1999), massa seca e emergência de plântulas no campo nas três localidades. O tempo de duração de cada teste foi também determinado. Os dados obtidos foram submetidos à análise de variância e as médias comparadas pelo teste Tukey a 5% de probabilidade. Dados da correlação entre resultados laboratoriais e desempenho germinativo no campo foram também determinados. Os resultados deste trabalho indicam que o produtor de sementes de soja dispõe de um número razoavelmente alto de testes entre os quais optar para avaliar, com um grau aceitável de confiança, o que esperar do desempenho germinativo de um lote de sementes quando semeado sob condições ambientais usuais para a prática agrícola. Os testes de maior precisão seriam os do envelhecimento artificial, o da condutividade elétrica e o do frio. Se, além da confiabilidade, ao produtor de sementes interessar também rapidez na obtenção de resultados, o teste da condutividade elétrica seria o mais...
Keywords: Soja; Merrill; Soja - Desempenho germinativo; Emergência em campo; Glycine max; Field emergence